Checkpoints and beyond - immunotherapy in colorectal cancer - Gutting, Tobias; Burgermeister, Elke; Härtel, Nicolai; Ebert, Matthias (Seminars in cancer biology, 2019)
Immunotherapy is the latest revolution in cancer therapy. It continues to show impressive results in malignancies like melanoma and others. At least so far, effects are modest in colorectal cancer (CRC) and only a subset of patients benefits from already approved checkpoint inhibitors. In this review, we discuss major hurdles of immunotherapy like the immunosuppressive niche and low immunogenicity of CRC next to current achievements of checkpoint inhibitors, interleukin treatment and adoptive cell transfer (dendritic cells/cytokine induced killer cells, tumor infiltrating lymphocytes, chimeric antigen receptor cells, T cell receptor transfer) in pre-clinical models and clinical trials. We intensively examine approaches to overcome low immunogenicity by combination of different therapies and address future strategies of therapy as well as the need of predictive factors in this emerging field of precision medicine.